2016
DOI: 10.1103/physrevlett.117.127001
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Resistivity Anisotropy in the Nematic Phase of FeSe

Abstract: The in-plane resistivity anisotropy is studied in strain-detwinned single crystals of FeSe. In contrast to other iron-based superconductors, FeSe does not develop long-range magnetic order below the nematic/structural transition at Ts ≈90 K. This allows for the disentanglement of the contributions to the resistivity anisotropy due to nematic and magnetic orders. Comparing direct transport and elastoresistivity measurements, we extract the intrinsic resistivity anisotropy of strainfree samples. The anisotropy p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
141
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(164 citation statements)
references
References 44 publications
21
141
2
Order By: Relevance
“…The temperature-dependent resistivity derivative-dρ/dT vs. T (inset in Figure 1b In previous studies, the tetragonal-to-orthorhombic reentrant transition was revealed by neutron and X-ray diffraction measurements [9,11] and high-resolution thermal-expansion and specific-heat measurements [8,10]. It should be pointed out that the orthorhombic distortion leads to the formation of structural domains in the LTO state, revealed and quantified by using polarized light microscopy [16][17][18][19][20]. Here, we use polarized light microscopy to study the temperature evolution of orthorhombic domain patterns in a single crystal of (Ba1 − xKx)Fe2As2 (x = 0.24).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The temperature-dependent resistivity derivative-dρ/dT vs. T (inset in Figure 1b In previous studies, the tetragonal-to-orthorhombic reentrant transition was revealed by neutron and X-ray diffraction measurements [9,11] and high-resolution thermal-expansion and specific-heat measurements [8,10]. It should be pointed out that the orthorhombic distortion leads to the formation of structural domains in the LTO state, revealed and quantified by using polarized light microscopy [16][17][18][19][20]. Here, we use polarized light microscopy to study the temperature evolution of orthorhombic domain patterns in a single crystal of (Ba1 − xKx)Fe2As2 (x = 0.24).…”
Section: Resultsmentioning
confidence: 90%
“…The contrast of the domain images is higher for larger difference in the rotation of the polarization plane between neighboring domains, proportional to the degree of orthorhombic distortion, δ = (a O − b O ) / (a O + b O ). Quantitative analysis of the images enables in determination of the orthorhombic order parameter [19,20]. This was not possible due to low contrast of the images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relation ρ < 0 is observed in the nonmagnetic nematic state for T S > T > T N , and even for T T S under the weak uniaxial stress. Remarkably, the opposite anisotropy ρ > 0 is realized in FeSe [18,19]. According to these observations, one may expect that the origin of nematicity in FeSe is special.…”
Section: Introductionmentioning
confidence: 83%
“…To answer this question, the strong in-plane anisotropy of transport coefficients has been studied intensively as a key electronic property in the nematic state [2,[15][16][17][18][19][20][21][22][23][24]. In Ba(Fe 1−x Co x ) 2 As 2 , Ba(As 1−x P x ) 2 and EuFe 2 (As 1−x P x ) 2 , large C 2 anisotropy in the resistivity ρ ≡ ρ x − ρ y < 0 appears in detwinned samples below T S , where ρ μ is the resistivity along the μ axis [15][16][17].…”
Section: Introductionmentioning
confidence: 99%